Toll-Like receptor signaling and the innate immune response - Fitzgerald, Kate (Henry Stewart Talks, 2012)
TLR signaling and innate immune response: Innate Immunity, Recognition of pathogen associated molecular patterns (PAMPs) such as LPS, Pattern recognition receptors (eg. TLRs) recognize microbial products, Effector cytokines driven by PRR signaling, Signaling intermediates employed downstream of TLRs, Counterregulation of TLR signaling as a mechanism to prevent excessive inflammation